Public Value and Public Administration - Bryson, John M. (John Moore), 1947-; Crosby, Barbara C., 1946-; Bloomberg, Laura (Book collections on Project MUSE., 2015)
Public administration practitioners and scholars around the globe are paying considerable attention to the creation of public value and to the health of the public sphere. However, there is little agreement about how to define public value and know if it is being achieved. Some definitions of public value focus on organizational effectiveness, efficiency, and accountability. Other definitions stress going beyond these qualities to also emphasize protecting and enhancing citizen rights and mutual obligations between the public and private sectors to society. This book explores competing visions of public value and what it means to discern, measure, and assess the creation of public value in a world where most major public challenges require contributions from governments, businesses, nonprofit organizations, and communities. In this book, scholars from the US, Europe, and Australia present an overview of major issues and debates focused on the skills, methods, measurements, and processes related to creating public value. This book is essential reading for public administration scholars, students, and practitioners.